Advertising ethics: A contextual response based on classical ethical theory - Pratt, Cornelius B. (Journal of business ethics, 1994)
F. P. Bishop argues that the ethical standard for advertising practitioners must be utilitarian. Indeed, the utilitarian theory of ethics in decision-making has traditionally been the preference of U.S. advertising practitioners. This article, therefore, argues that the U.S. advertising industry's de-emphasis of deontological ethics is a reason for its continuing struggle with unfavorable public perceptions of its ethics — and credibility. The perceptions of four scenarios on advertising ethics and the analyses of the openended responses of 174 members of the American Advertising Federation to those scenarios suggest that advertising practitioners need a stricter adherence to deontological ethics than is indicated in this study.